Effect of Antioxidant and Pro-oxidant on the Stability of Microencapsulated Squalene by Spray Drying - Dwi Ayuni; Joko Nugroho Wahyu Karyadi; Arifin Dwi Saputro; Hidefumi Yoshii (agriTECH, 2021)
Natural hydrocarbon compounds are extremely in high demand across various applications. For instance, squalene (SQ) is widely used in cosmetic and food supplement industries, due to beneficial health components. The aim of this study was to investigate the potentials of antioxidant addition on the physical properties, as well as SQ stability in spray-dried powder at various oil droplet diameters (0.3 – 4 µm). Rosemary oil extract served as antioxidant, while iron (II) sulfate accelerated the oxidation. Subsequently, SQ stability was evaluated at four separate temperatures, termed 25, 50, 70, and 105°C, after one month storage. Also, the morphological structures of the samples were characterized with scanning electron microscopy (SEM). The results showed the oil droplet diameter influenced the physical properties of SQ, as lesser drip sizes were known to enhance material strength. Furthermore, antioxidant inclusion proved to be effective in inhibiting oxidation, particularly in powders with extensive oil droplet diameter. Therefore, high regression coefficients (R2 > 0.97) and reduced chi-square confirmed Weibull model acceptance in predicting the retention of SQ content.